2001
DOI: 10.1248/bpb.24.1437
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyphenols on Calcium Content and Alkaline Phosphatase Activity in Rat Femoral Tissues in Vitro.

Abstract: This loss may be due to increased bone resorption and decreased bone formation. Osteoporosis with a decrease in bone mass is widely recognized as a major public health problem.4) The most dramatic expression of this disease is represented by fractures of the proximal femur. Pharmacological and nutritional factors may prevent bone loss with increasing age. 5,6) The chemical compounds in food that act on bone metabolism, however, are poorly understood.Genistein is a natural isoflavonoid phytoestrogen found in Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 27 publications
(37 reference statements)
3
22
0
Order By: Relevance
“…On the other hand, GTE caused a decrease in ALP activity, often reducing the activity levels by ≥50% in wells with no GTE added. This is in agreement with Yamaguchi and Ma [2001] concerning the effect of polyphenols on ALP activity in rat femoral tissues; they concluded that EGCG (0.1 mM) significantly inhibited ALP activity.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, GTE caused a decrease in ALP activity, often reducing the activity levels by ≥50% in wells with no GTE added. This is in agreement with Yamaguchi and Ma [2001] concerning the effect of polyphenols on ALP activity in rat femoral tissues; they concluded that EGCG (0.1 mM) significantly inhibited ALP activity.…”
Section: Discussionsupporting
confidence: 90%
“…5 mM-EGCG. In contrast to all these studies Yamaguchi & Jie (2001) have observed no positive effects of either catechin or EGCG (0 . 1-100 mM) on either bone calcification or alkaline phosphatase activity in femoral diaphyseal and metaphyseal tissues of rats in vitro.…”
Section: Catechin and Related Flavanolsmentioning
confidence: 67%
“…We determined the effect of polyphenols [glycitein, resveratol, quercetin, catechin, and (-)-epigallocatechin gallate (EGCg)] on bone calcification in vitro. 20) Of various polyphenols used, genistein was found to have a unique anabolic effect on bone calcification as shown in Fig. 2.…”
Section: Anabolic Effect Of Isoflavone On Bone Metabolism In Tissue Cmentioning
confidence: 99%
“…20) Resveratol, catechin, and (-1)-epigallocatechin gallate, which are polyphenols in food, do not have an anabolic effect on bone calcification. 20) A phytoestrogen genistein has a unique anabolic effect on bone metabolism.…”
Section: Prospectsmentioning
confidence: 99%